Handheld app offering visual support to students with autism spectrum disorders (ASDs) - Zamfir, Bogdan; Tedesco, Robert; Reichow, Brian (International Conference on Computers Helping People with Special Needs, 2012)
iPrompts® is a software application for handheld devices that provides visual support to individuals with Autism Spectrum Disorders (ASDs). Caregivers use the application to create and present visual schedules, visual countdown timers, and visual choices, to help individuals with ASDs stay organized, understand upcoming events, and identify preferences. The developer of the application, HandHold Adaptive, LLC, initially introduced iPrompts on the iPhone and iPod Touch in May of 2009. The research team from the Center of Excellence on Autism Spectrum Disorders at Southern Connecticut State University conducted a study of iPrompts in 2010, investigating its use by educators working with students with ASDs. Among other findings, educators indicated a desire to present visual supports on a larger, "tablet"-sized display screen, leading the developer to produce an iPad-specific product, iPrompts® XL. Described in this paper are the research effort of iPrompts and subsequent development effort of iPrompts XL. © 2012 Springer-Verlag.
7 citations (Crossref) [2023-10-31] tex.type: Proceedings paper
Keywords: ASD; Applications; Autism spectrum disorders; Diseases; Education; Hand held computers; Hand held device; Smartphones; app; application; autism spectrum disorder; dept.aa; handheld device; iPad; iPhone; iPrompts; smartphone; tablet

Using handheld applications to improve the transitions of students with autism spectrum disorders - Ben-Avie, Michael; Newton, Deborah; Reichow, Brian (Innovative Technologies to Benefit Children on the Autism Spectrum, 2014)
While the knowledge that has been gained from previous studies has accelerated the understanding of the difficulties facing individuals with Autism Spectrum Disorders (ASDs), there is concern regarding the speed with which and the overall lack of translation of research into interventions that make differences in the everyday lives of individuals with ASDs (Gresham, et al., 2001; Volkmar, et al., 2004; Volkmar, Reichow, & Doehring, 2011). For example, the symptoms of ASDs can greatly impair an individual’s ability to navigate independently through everyday events. Translating this knowledge into instructional practice requires, then, the design of methods for easing students’ transitions within the school, home, and community. While research has validated the use of low-tech visual supports (e.g., National Autism Center, 2009), little has been done to analyze the utility and appropriateness of high-tech assistive technology, such as those interventions administered through smartphones, tablets, and other handheld devices, which are devices that are being used more frequently in education settings (Gray et al., 2010). This chapter presents the results of federally funded research to determine whether the use of iPrompts—a software application for iOS and Android-based smartphones and tablet computers—assists teachers and other educational professionals as they help students with ASD transition from one activity to the next or from one setting to another.
Citation Key Alias: pop00300
Keywords: Aluminum alloys; Application programs; Assistive technology; Autism spectrum disorders; Diseases; Education; Hand held device; Handhelds; High tech; Instructional practices; Smartphones; Software applications; Students; Tablet computer; Teaching; dept.sed

Practicing Evidence-Based Practices - Eren, Ruth Blennerhassett; Brucker, Pamela Owen (Evidence-Based Practices and Treatments for Children with Autism, 2011)
Public education in the United States has a history of local control in the development of curriculum and instruction. Although notable court decisions have led to more universal applications of educational policy and practices (Brown v. Board of Education 1954, Oberti v. Clementon 1993), it has been federal law that has resulted in significant changes in instruction. The Individuals with Disabilities Education Improvement Act (IDEA; Public Law 108–142), first enacted in Public Law 94–142, guaranteed the right of a free, appropriate public education for all children, regardless of the severity of their disability. The word “appropriate” resulted in the beginning of what we refer to today as differentiated instruction: instructional strategies that allow a child to learn and progress in an educational setting. The federal law, No Child Left Behind (NCLB; Public Law 107-110), enacted in 2001, contributed to this initiative and added a caveat that these differentiated instructional strategies needed to be grounded in scientifically based research. Indeed, the term “scientifically based research” has been noted to appear in NCLB 111 times (Deshler 2002). The federal government, in IDEA 2004, identified 13 eligibility categories. In order to receive special education services, a student must, through a multidisciplinary evaluation, meet the eligibility criteria established for one of the 13 categories. Since 1975, when PL94–142 was enacted, educational interventions for students receiving special education have expanded, particularly in disability categories with a high level of incidence such as speech and language disorders and learning disabilities. Low-incidence disabilities, such as mental retardation, visual impairments, and autism, have received less attention.
Citation Key Alias: lens.org/104-519-704-094-108
Keywords: General Education; Individualize Education Program; Special Education; Special Education Teacher; Team Meeting; dept.sed